Effects of verapamil combinations with enalapril or indapamide on plasma, vascular and platelet hemostasis and biochemical markers of endothelial dysfunction in patients with arterial hypertension and metabolic syndrome - N. M. Krasnova; T. P. Kalashnikova; A. I. Vengerovsky; E. M. Idrisova; I. V. Kulagina; T. E. Suslova; O. V. Gruzdeva; S. V. Kremeno; N. M. Zheltonogova; A. A. Shishkina; R. S. Karpov (Российский кардиологический журнал)
The combination of verapamil retard and enalapril, or verapamil retard and indapamide SR similarly and significantly increased high-density lipoprotein cholesterol and stable NO2 metabolite levels, reducing platelet aggregation in patients with metabolic syndrome (MS). Compared to the combination of verapamil retard and indapamide SR, the combination of verapamil retard and enalapril significantly reduced atherogenicity coefficient, glycated hemoglobin, glucose and soluble fibrin-monomer complex levels, increasing nitrite concentration and activating plasminogen.